2019
DOI: 10.3389/fcell.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring of Memory Circuits: Connecting Adult Newborn Neurons With the Help of Microglia

Abstract: New neurons are continuously generated from stem cells and integrated into the adult hippocampal circuitry, contributing to memory function. Several environmental, cellular, and molecular factors regulate the formation of new neurons, but the mechanisms that govern their incorporation into memory circuits are less explored. Herein we will focus on microglia, the resident immune cells of the CNS, which modulate the production of new neurons in the adult hippocampus and are also well suited to participate in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 154 publications
(304 reference statements)
1
63
0
Order By: Relevance
“…6) to quantify the average area covered by cells positive for each of these antibodies, as well as their colocalization. The "inner" (bordering the hilus) and "outer" ROIs of the dentate gyrus were created separately, as microglia activity in these subregions could be differentially regulating neurogenesis (Gemma and Bachstetter, 2013;Rodríguez-Iglesias et al, 2019).…”
Section: Quantification Of Microglia-related Measuresmentioning
confidence: 99%
“…6) to quantify the average area covered by cells positive for each of these antibodies, as well as their colocalization. The "inner" (bordering the hilus) and "outer" ROIs of the dentate gyrus were created separately, as microglia activity in these subregions could be differentially regulating neurogenesis (Gemma and Bachstetter, 2013;Rodríguez-Iglesias et al, 2019).…”
Section: Quantification Of Microglia-related Measuresmentioning
confidence: 99%
“…We found that phagocytosis of apoptotic cells reprogrammed microglia towards a neurogenic modulatory phenotype that was mostly related to their secretome, as the majority of the modulatory genes encoded secreted proteins, including neuropeptides such as VGF, and growth factors such as VEGF and FGF2, some of which have already been described to participate in the microglial regulation of neurogenesis (Kreisel et al, 2018). In addition, the microglial secretome may contain metabolites, miRNAs and extracellular vesicles, which may also alter neurogenesis (Rodriguez-Iglesias et al, 2019). When administered in vivo, the acute secretome of phagocytic microglia inhibited hippocampal neurogenesis, as it had an early tendency to decrease rNSCs that was later followed by a reduction in mature neuroblasts.…”
Section: Microglia Regulates Neurogenesis Through the Phagocytosis Sementioning
confidence: 84%
“…Furthermore, we found that both LPS and the secretome of LPS-stimulated microglia enhanced the production of neuroblasts in vitro, suggesting that inflammation is not as detrimental for neurogenesis as previously stated (Ekdahl et al, 2003;Monje et al, 2003) and that cytokines were not responsible for the effects of phagocytic microglial secretome on neural-committed cells. In addition, the neurogenic modulatory program initiated by phagocytosis encompassed genes involved in matrix remodeling (matrix metalloproteases) and membrane ligands (Jag1, ligand for Notch receptor), suggesting that the observed direct contact between microglia and rNSCs/neuroblasts (Sierra et al, 2010) may also participate in shaping the neurogenic niche through participating in the local control of neuroblast differentiation, survival and synaptic integration (Rodriguez-Iglesias et al, 2019).…”
Section: Cytokines Are Unrelated To the Effect Of Phagocytosis Secretmentioning
confidence: 99%
“…Furthermore, the inhibition of TXNIP‐associated oxidative stress attenuated the cognitive impairment in a model of vascular dementia . Considerable evidence indicates that microglia play a key role in synaptic plasticity, learning, and memory via the release of TNF‐α in a model related to fear memory, the production of lactate, and the modulation of structural plasticity such as LTD, synaptic pruning, axonal and dendritic growth . Thus, combining all the aforementioned findings, it is conceivable that lactate acts as a signaling molecule in synaptic plasticity and memory via modulating microglia in a neuronal activity‐dependent manner.…”
Section: Lactate As a Signaling Moleculementioning
confidence: 99%
“…Cocaine-induced CPP [11,48,53,54] In [11,40,44,45,48,56] In dorsal hippocampus, increased Arc protein [57][58][59][60] www.advancedsciencenews.com www.bioessays-journal.com pruning, axonal and dendritic growth. [66][67][68] Thus, combining all the aforementioned findings, it is conceivable that lactate acts as a signaling molecule in synaptic plasticity and memory via modulating microglia in a neuronal activity-dependent manner.…”
Section: Mediate Actin Reorganization and Amparsmentioning
confidence: 99%